Mitochondria as Regulators of Nonapoptotic Cell Death in Cancer - Saloni Malla; Rabin Neupane; Saloni Sood; Noor Hussein; Mariam Abou‐Dahech; David Terrero; Charles R. Ashby Jr.; R. Jayachandra Babu; Amit K. Tiwari (MedComm)
ABSTRACT Mitochondria are involved in cell survival and metabolic processes including adenosine triphosphate production, heme biosynthesis, reactive oxygen species, and iron and calcium homeostasis. Although mitochondria are well known to contribute to apoptosis, a growing body of evidence indicates that mitochondria modulate nonapoptotic cell death (NACD) mechanisms, including autophagy, necroptosis, ferroptosis, paraptosis, pyroptosis, parthanatosis, and cuproptosis. These NACD pathways differ in molecular triggers, morphological characteristics, and immunological consequences, but they all involve mitochondria. For example, mitochondrial ROS and lipid peroxidation play a role in ferroptosis, whereas mitochondrial depolarization and the release of apoptosis inducing factor are paramount to parthanatosis. Mitochondrial swelling is a hallmark of paraptosis, whereas mitochondrial disruption is associated with pyroptosis. Autophagy, though primarily a survival mechanism, is also regulated by mitochondrial dynamics in cancer cells. In cuproptosis, mitochondrial protein aggregates when iron–sulfur cluster proteins are disrupted, resulting in copper‐dependent cell death. There are many factors that influence NACD, including mitochondrial membrane potential, bioenergetics, calcium flux, metabolites, and interactions with the endoplasmic reticulum. The review comprehensively summarizes our understanding of mitochondrial and NACD interactions, particularly in cells resistant to classical apoptosis agents. Therapeutic vulnerabilities associated with mitochondria‐mediated NACD could lead to next‐generation therapies.